Efektivitas Aplikasi Kippin School 4.0 Untuk Menambah Semangat Belajar Siswa SD / MI - M. Dwi Prastiawan; Kristina Gita Permatasari (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
The results of this research aim to analyze the development of enthusiasm for learning in class VI students of Madrasah Ibtidaiyah Negeri Blora at home. The method used in this research is a quantitative approach using interview and observation techniques. Interview conducted with sixth grade teacher. This research was carried out at Madrasah Ibtidaiyah Negeri Blora, using 30 grade VI students as subjects. At class meetings, there are 3 stages, namely socialization, implementation and reflection. Based on the research results, it was found that 85% of the 30 students were able to download the application smoothly. Furthermore, 95% of the 30 students were able to use the application well and have fun. So the Kippin School application in student learning at home is able to foster student enthusiasm and motivation for learning. Keyword: Effectiveness, Kippin School 4.0 Application, Enthusiasm for Learning